On the near-wake of a ground-effect diffuser with passive flow control - Ehirim, Obinna; Knowles, Kevin; Saddington, Alistair J.; Finnis, Mark V.; Lawson, Nicholas J. (Springer, 2019)
A ground-effect diffuser is an upwardly-inclined section of an automobile’s underbody which increases aerodynamic performance by generating downforce. To understand the diffuser flow physics (force behaviour, surface and off-surface flow features), we established the near-wake (within one vehicle width of the base) velocity profiles and flow structures of an automotive ground-effect diffuser using a bluff body with a 17 degree slanted section forming the plane diffuser ramp surface (baseline geometry), and endplates extending along both sides of the ramp. Wind tunnel experiments were conducted at a Reynolds number of 1.8 million based on the bluff body length, and laser Doppler velocimetry was used to measure two-dimensional velocity components on three planes of the diffuser near-wake. We also measured the velocity field in the near-wake of diffusers with modified geometry (with an inverted wing or a convex bump) as passive flow control devices. The near-wake velocity profiles indicated that the passive flow control methods increased the diffuser flow velocity and that the longitudinal vortices along the diffuser determined the shape of the flow structures in the near-wake of the diffuser bluff body
Keywords: Laser Doppler Velocimtery; Ground Effect; Diffuser; Flow Control